(3OjhGf GdCSYQOis - (3CHh HcQ fhQ GdOjf eMeO Hf eMeO Hf YHO GdYRjR Hf YHO GdUeO Hf QSJe,J (B656 (3g` s
(3ChdgG (B:s
(3HfXe LYdJ GdChLR CSeGdg abO JfGSH HGdJMbjb daXkG hebUOkG s
(3BNQgG (B:s
(3BNQ GdehLhO efg ai TQM bhdg (B: (3hMi eTJbi jQb GdjQbGf Ud Hg GdhjdGJ hGdCfGI eQjOG hBNQ GdehLhO ef GdTQM (B: ( (3hjbGd ddeQCI GdHWjFI GdbjGe dSefgG CfGI hhfGI , cCf GdChd ef GdKGfi hcCf GdKGfi ef Gdhfi hgh (B) s
(3GdfSNI HgG MhGTs
(3QJHg Ydi GdehVhYGJs
(3hHOCg HGdfGUQjGJ ai eOM UdGM GdOjf GdCjhHi eTQhM GdCHjGJs
(3fSNI NRGFfjI HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
Keywords: (3GdCOHs